Theoretical investigation of Ree–Eyring nanofluid flow with entropy optimization and Arrhenius activation energy between two rotating disks. (August 2019) - Hayat, T.; Khan, Sohail A.; Ijaz Khan, M.; Alsaedi, A.
Highlights: Flow of Ree–Eyring nanofluid between two rotating disks is considered. Heat transfer Characteristics are discussed through viscous dissipation and heat source/sink. Behaviors of Brownian motion and thermophoresis effects are also discussed. Total entropy rate is calculated through second law of thermodynamics. Abstract: Background and objective: Improvement of high performance thermal systems for heat transport augmentation has become quite prevalent nowadays. Various works have been performed to pick up a comprehension of the heat transport execution for their practical utilization to heat transport augmentation. Therefore, the nanomaterial has been used in flow of Ree-Eyring fluid between two rotating disks for thermal conductivity enhancement of base fluid. Heat transfer characteristics are discussed through viscous dissipation and heat source/sink. Behaviors of Brownian motion and thermophoresis are also examinted. Physical behaviors of irreversibility in nanofluid with Arrhenius activation energy are also accounted. Methods: The nonlinear systems lead to ordinary differential problems through implementation of appropriate transformations. The relevant problems are tackled by (OHAM) Optimal homotopic method for series solutions. Results: Effects of various physical parameters on the velocity, entropy rate, Bejan number, concentration and temperature are discussed graphically. Skin friction coefficient and gradient of temperature are numerically examined and discussed with various parameters. Conclusions: Entropy generation rate is control by minimizing the values of Brinkman number and stretching parameter. Entropy rate and Bejan number show the dual behaviors against Eckert number. Both decay near the lower disk while reverse holds near the upper disk. Entropy rate and Bejan number show similar behaviors for Weissenberg number.